2009
DOI: 10.1007/s00508-009-1137-3
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of febrile gastroenteritis associated with jellied pork contaminated with Listeria monocytogenes

Abstract: In September 2008, the Austrian Agency for Health and Food Safety (AGES) learned of an outbreak of diarrheal illness that included a 71-year-old patient hospitalized for gastroenteritis with a blood culture positive for Listeria monocytogenes. Three stool specimens provided by seven of 19 persons attending a day trip to a foreign city, including a final break at an Austrian tavern, yielded L. monocytogenes. All isolates were of serovar 4b and had fingerprints indistinguishable from each other. A cohort study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 19 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…In particular, susceptible individuals, like pregnant women, newborns, immunocompromised patients, and the elderly, are at risk of developing invasive listeriosis that can arise with septicemia or meningitis and is often complicated by encephalitis, abortion, and perinatal infections (5). A gastrointestinal form of the disease is also reported and referred to as noninvasive listeriosis (6)(7)(8). L. monocytogenes is widely diffused in the environment and, like other species of the genus Listeria, its natural habitat is soil, preferably in the presence of decaying vegetation; these bacteria can also be harbored in the intestinal tracts of humans (9), various domestic animals, like ruminants, pigs, and poultry, and wild species (10).…”
mentioning
confidence: 99%
“…In particular, susceptible individuals, like pregnant women, newborns, immunocompromised patients, and the elderly, are at risk of developing invasive listeriosis that can arise with septicemia or meningitis and is often complicated by encephalitis, abortion, and perinatal infections (5). A gastrointestinal form of the disease is also reported and referred to as noninvasive listeriosis (6)(7)(8). L. monocytogenes is widely diffused in the environment and, like other species of the genus Listeria, its natural habitat is soil, preferably in the presence of decaying vegetation; these bacteria can also be harbored in the intestinal tracts of humans (9), various domestic animals, like ruminants, pigs, and poultry, and wild species (10).…”
mentioning
confidence: 99%
“…Foodborne transmission of L. monocytogenes can also cause a self-limiting acute gastroenteritis (in immunocompetent persons). From the data available in normal hosts in Italy, Illinois (USA) and Austria, it appears that febrile gastroenteritis in normal hosts requires the ingestion of a high dose of several million bacteria (Aureli et al 2000;Dalton et al 1977;Pichler et al 2009). Grif et al studied the incidence of fecal carriage of L. monocytogenes in healthy volunteers (Grif et al 2003).…”
Section: Disease Symptoms In Humansmentioning
confidence: 98%
“…Different food sources particularly poultry, red meat and meat products have been associated with outbreaks as well as sporadic cases (Billie et al, 2006;Pichler et al, 2009;El-Malek et al, 2010). Other studies reported vegetable products especially cabbage as a source of contamination and retrospective study, revealed that sheep manure from a flock diagnosed earlier with listeriosis was used to fertilize the crop (Schlech et al, 1983;Rocourt et al, 2001).…”
Section: Listeria Speciesmentioning
confidence: 99%